Trade in services in the Baltic States: evolution and future prospects - Rodríguez, Mercedes; Melikhova, Yulia; Camacho, José A. (Technological and Economic Development of Economy, 2018)
Trade in services in the Baltic States has traditionally been overlooked. The main objective of this article is to assess the current situation and the future prospects of trade in those services used as intermediate inputs using data from the World Input-Output Database. Unlike previous works we do not only analyze direct trade but also indirect trade, that is, the trade in intermediate services contained in goods. The results show that although traditional services reported major shares in the total volume of intermediate services exports in the Baltic States, other categories of more knowledge-intensive services are gaining importance. First published online: 08 Jun 2017